What are we talking about when we talk about care? A conceptual review of the literature - São José, José (2017)
The primary aim of this article is to make a contribution to clarify the concept of ?care? in the field of care for older people, by reviewing and discussing the conceptual literature and, based on this, by proposing a new unified definition. The secondary aim of this article is to trace, in general terms, the evolution of the empirical research on care for older people, presenting at the same time, possible avenues for future research. It is expected that a new unified definition of the concept of care may contribute to a better operationalization of it, enhancing the reliability and validity of future research and the potential for comparative analysis and theory development.